Grey systems : theory and applications - Chen, Mian-Yun (Kybernetes, 2004)
In this paper, we take a look at the state-ofthe- art of the theory and applications of the so-called grey systems theory founded in the 1980s. After a brief historical review of the development history of this theory, we look at the main blocks of the theory followed by several successful applications. It is our hope that a reader who does not know anything about this branch of scientific exploration will gain a firm understanding of the basics so that the rest of this special issue becomes possible to comprehend.